Adapting to Climate Change in Vietnam: Insights from a Structural Model - Hosny, Amr (Asian Journal of Economic Modelling, 2021)
Vietnam is increasingly exposed to climate change. The COVID-19 crisis offers an opportunity to push for green investment and climate-resilient adaptation. In this context, the paper uses a DSGE structural model, calibrated to features of the Vietnamese economy, to simulate the macroeconomic trade-offs of investing in resilient infrastructure. Compared to scenarios of a baseline no policy change and additional standard infrastructure spending, the model findings illustrate the long-term benefits of adaptation infrastructure investments on growth and public debt dynamics. Specifically, while adaptation infrastructure is initially slightly costlier during the scale-up period, it can better withstand natural disaster shocks, and over time, would have lower maintenance costs and higher return than conventional infrastructure. Other model scenarios illustrate the trade-offs of different financing sources as well as the benefits of public financial management reforms that improve investment efficiency.